Political Image of Russian in Cycles of Ideological opposition with the West - O. A. Nesterchuk; A. G. Lazebnik (Проблемы постсоветского пространства, 2017)
In the article the of home policy and foreign-policy image of Russia is examined on a background Russian-western ideological contradictions. Reasons of negative perception of character of the Russian state are distinguished by western researchers and population. The historical comparative analysis of internal despotism and external aggressiveness of the states is presented in the days of the rule of Ivan IV, some European monarchs by the aim of understanding of essence of the mythologized negative idea about Russia in the west.